Reviews. Issue 3 (1st October 2019) - Felando, Cynthia; Zeitz, Christian David
Exploring Television Acting, Tom Cantrell and Christopher Hogg (eds) (2018) London: Continuum, 206 pp., ISBN 9781474248587, h/bk, £75Technicolored: Reflections on Race in the Time of TV, Ann DuCille (2018) Durham: Duke University Press, 352 pp., ISBN 9781478000396, h/bk, $104.95; p/bk, $27.95